Techical-economic performance of consortium systems of the common-bean intercalated with newly planted coffee tree (Coffea arabica L.) - Carvalho, Abner José de; Andrade, Messias José Bastos de; Guimarães, Rubens José; Reis, Ricardo Pereira (Coffee Science - ISSN 1984-3909, 2008)
Aiming to study the economic return of systems of production of common-bean (Phaseolus vulgaris L.), intercalated with the newly-planted coffee tree, one field experiment was carried out in the Federal University of Lavras, in coffee crops of the cultivar Catucaí (line 3SM), newly planted. The common-bean cultivar BRS-MG-Talismã was used. The experimental design was in randomized blocks with three replicates and 4 x 4 + 2 factorial scheme, involving four number of rows of bean plant (one, three, four and six intercalary rows) and four doses of fertilization of the legume (0%, 50%, 100% and 150% of the fertilization recommended), plus two additional treatments (the monocultivation either of the coffee trees and bean plants). The results allow to conclude that the increase of the number of bean rows, especially starting from four rows, provides smaller increment in the diameter of the stem of the coffee plant, reduces the medium total costs of common-bean production and of formation of the coffee plant, mainly up to four rows, and it increases the profit obtained with the common-bean production. Therefore, the use of up to four intercalary rows of common-bean plant would be indicated, becomes possible the covering of 65% of the costs of formation of the coffee tree to up to six months of age. The increment of the planting manuring and covering of the common-bean plants to up to 150% of the dose recommended doesn’t influence the income of the common-bean in consortium with the coffee (Coffea arabica L.) newly-planted, increasing the medium cost of common-bean production. However, the absence of manuring of the common-bean provokes more mortality of plants of coffee in the measure in that increases the number of bean rows.